Decompressive Craniectomy For Severe Diffuse Traumatic Brain Injury. Study of 25 Cases (Medical Forum Monthly, 2023)
Objective: To study association between serum uric acid level and hypertension in different age groups of semiurban population of Karachi.Study Design: Cross sectional studyPlace and Duration of Study: This study was conducted at the Department of Medicine, Fatima Hospital, Baqai Medical University Karachi from 15th December 2022 to 15th February 2023.Materials and Methods: 366 participants aged more than 40 years were enrolled in the study. It was ensured participants were not using any drug that may affect serum uric acid level and were not suffering from any comorbid condition like liver or kidney disease that may increase serum uric acid level. After a brief physical examination blood sample was sent for serum uric acid and lipid profile. Appropriate statistical test was used to find association of serum uric acid and blood pressure readings.Results: Serum uric acid level (p = 0.046), Systolic blood pressure (p=0.006) and diastolic blood pressure (p=0.032) were significantly high in participants aged more than 60 years. Prevalence of hypertension was higher among participants with hyperuricemia as compared to participants with normal uric acid level.(65% vs 52.14%, p = 0.021).Conclusion: Hyperuricemia is associated with increased prevalence of hypertension.